Relationship of Combat Experiences and Alcohol Misuse Among U.S. Special Operations Soldiers. Issue 3 (1st March 2014) - Skipper, Leonard D.; Forsten, Robert D.; Kim, Eugene H.; Wilk, Joshua D.; Hoge, Charles W.
ABSTRACT: This study examined the association between specific combat experiences and postdeployment hazardous drinking patterns on selected military populations that are considered high risk, such as personnel belonging to U.S. Army Special Operations Forces. Data collection were conducted in a 5-year span in which 1, 323 Special Operations Forces Soldiers were surveyed anonymously from 3 to 6 months after returning from deployment to Iraq/Afghanistan regarding their combat experiences and mental health. Combat items were independently analyzed and placed into the following categories: (1) Fighting, (2) Killing, (3) Threat to oneself, (4) Death/Injury of others, and (5) Atrocities. Alcohol misuse was measured using the Alcohol Use Disorders Identification Test-Consumption. Of the Soldiers sampled, 15% ( N = 201) screened positive for alcohol misuse 3 to 6 months postdeployment. Combat experiences relating to fighting, threat to oneself, and atrocities were significantly related to alcohol misuse when analyzed individually. However, when factors were analyzed simultaneously, combat experiences in the fighting category were significantly associated with a positive screen for alcohol misuse. In conclusion, Soldiers belonging to certain elite combat units are significantly more likely to screen positive for alcohol misuse if they are exposed to specific types of fighting combat experiences versus any other type of combat exposure.